Improving the ability to recognize alphabet letters through flannel board media at the RA Kartini Segara Katon State Kindergarten, Indonesia - Suari, Etin Indra; Ramzi, Muhajirin; Wathoni, Hizbul (Nashir Al-Kutub Indonesia, 2023)
This research aims to improve the ability to recognize alphabet letters through flannel board media at TKN RA Kartini Segara Katon for the 2024/2024 academic year.This research was carried out at TKN RA Kartini Segara Katon in group B with a total of 17 children consisting of 8 boys and 9 girls.This research uses the Classroom Action Research (PTK) method.This research uses data collection techniques, namely observation, interviews and documentation.The data analysis techniques used are qualitative and quantitative techniques.Research can be said to be successful if it reaches a score of 80%. The results of the research conducted showed that the use of flannel board media on the ability to recognize alphabet letters in pre-action or pre-cycle only reached 41%, in cycle I it increased to 58% and in cycle II it increased to 88%.So it can be concluded that choosing learning media is very important in improving the ability to recognize alphabet letters because if the learning media presented is interesting it will make children more focused and attract children's attention to the learning delivered by the teacher, especially learning the ability to recognize letters.The research was stopped in cycle II because it had reached the success criteria.